Improved Versions: Feminist Poetics and Recent Work by Ulla Hahn and Ursula Krechel - Charlotte Melin (Studies in 20th & 21st Century Literature, 1997)
This essay analyzes how Ulla Hahn and Ursula Krechel in their recent poetry and essays have drawn a connection between feminism and their writing. The feminine/feminist outlook they advance is exemplary for their generation of women authors because they have sought to expand the poetic canon by interrogating assumptions made by modernism. A reappraisal of their poetry suggests that interpretations of their work must take account of the feminist poetics of these authors.
Keywords: Ulla Hahn; Ursula Krechel; poetry; essays; connection; feminism; writing; feminine; feminist; generation; women authors; poetic canon; expant; poetic; modernism; feminist poetic